Acute, subacute oral toxicity and Ames test of Py-mulin: an antibacterial drug candidate - Yuan Fan; Yunxing Fu; Yuhang Zhou; Yu Liu; Baocheng Hao; Ruofeng Shang (BMC, 2022)
Abstract Background Py-mulin is a new pleuromutilin derivative with potent antibacterial activities in vitro and in vivo, suggesting this compound may lead to a promising antibacterial drug after further development. The present study is aimed to evaluate the acute and subacute oral toxicity, and the genotoxicity with the standard Ames test according to standard protocols. Methods Acute oral toxicity of Py-mulin was determined using Kunming mice. The 28-day repeated dose oral toxicity study in SD rats was performed according to OECD guideline No. 407. The bacterial reverse mutation (Ames test) was carried out using four Salmonella typhimurium (S. typhimurium) strains TA97, TA98, TA100 and TA1535 with and without S9 metabolic activation. Results The LD50 values in acute oral toxicity were 2973 mg/kg (female mice) and 3891 mg/kg (male mice) calculated by the Bliss method. In subacute toxicity study, 50 mg/kg Py-mulin did not induce any abnormality in body weight, food consumption, clinical sign, hematology, clinical chemistry, organ weight, and histopathology in all of the treatment groups. However, high doses of Py-mulin (100 and 300 mg/kg) displayed slightly hepatotoxicity to female rats. Furthermore, Py-mulin did not significantly increase the number of revertant colonies of four standard S. typhimurium strains with the doses of 0.16-1000 μg/plate in the Ames study. Conclusions Based on our findings, our study provides some information for the safety profile of Py-mulin.